TITANIUM DIOXIDE SUSPENSION PHOTOCATALYSIS IN A TUBULAR PHOTOREACTOR AND TITANIUM DIOXIDE REUSE ON THE REMOVAL OF PHENOL - Suryaman, Dhanus (Jurnal Air Indonesia, 2008)
We studied flow rate, electrolytes effects, titanium dioxide separation and reuse and sunlight application on photocatalysis in a tubular photoreactor integrated with the titanium dioxide separation/reuse. The circulative flow treatment was preferred over the single pass treatment. Phenol and TOC removals in tap and deionized waters were a maximum at the circulative flow rate of 600 ml min-1 and the transmittance of 0.26%. At low flow rate, titanium dioxide particles were sedimented in tap water, but those were perfectly suspended in deionized water. The titanium dioxide slurry was sedimented spontaneously by standing and was repeatedly reused without decreasing the degradation efficiency. Ã‚Â Keywords : Photocatalytic, Optimum flow, Electrolytes, Separation, SolraÃ‚Â